Detection of antioxidant constituents from Persicaria hydropiper using LC-UV-DAD-ESIM/MS. - Noor Hashim, Noor Haslinda (2011)
The antioxidant activity of the crude methanolic extract and fractions of the aerial parts of Persicaria hydropiper or ‘kesum’ were investigated to evaluate their potential application as health supplement. Dried aerial part of the plant samples were extracted with methanol and the methanol crude extract was fractionated by liquid-liquid extraction into five different fractions. All fractions were analyzed for total phenolic content utilizing Folin Ciocalteau assay. The antioxidative potential of all fractions were also evaluated using 1,1-diphenyl-2-picryhydrazyl radical (DPPH), ferric thiocyanate (FTC) and xanthine oxidase inhibition (XO) methods. Furthermore, the metabolite profiling of the bioactive antioxidant fractions was accomplished using liquid chromatography coupled with mass spectrometry (LCMS). The use of LCMS techniques is an important approach for online identification of plant constituents. The amount of the total phenolics, varied widely in the fractions and ranged from 0.00 to 224.4 mg GAE/100 g dry extract. The highest level was found in butanol fraction with 224.4 mg GAE/100 g dry extract, followed by ethyl acetate (68.9 mg GAE/100 g dry extract), dichloromethane (8.7 mg GAE/100 g dry extract), aqueous (6.4 mg GAE/100 g extract) and hexane (4.3 mg GAE/100 g dry extract) fractions. The DPPH assay revealed that the ethyl acetate and butanol fractions of P. hydropiper were the most active fractions with IC50 values of 25.5 and 28.6 μg/ml, respectively. Dichloromethane fraction showed moderate activity with IC50 value of 94.2 μg/ml. The lower radical scavenging activity was observed in aqueous and hexane fractions with IC50 values ranged from 110 to 380 μg/ml. In comparing the antioxidant activity using ferric thiocyanate assay, all fractions effectively inhibited higher lipid oxidation compared to α-tocopherol. Except for the hexane fraction, the inhibition of the other fractions were comparable to the known synthetic antioxidant, butylated hydroxytoluene (BHT). Of the fractions assayed for xanthine oxidase inhibitory activity, butanol fraction showed the most active with IC50 value of 32.3 μg/ml followed by ethyl acetate fraction with IC50 value of 166.9 μg/ml. The ethyl acetate and butanol fractions exhibited good antioxidant activity in all the assay tested. The LC-DAD-ESIMS chemical profiling method was developed for the identification of phytochemical constituents in the antioxidative fractions of P. hydropiper. The phytochemical profile of ethyl acetate fraction has identified fourteen compounds together with two unidentified compounds. The compounds were identified as quercetin (1), quercetin-3-O-glucoside (3), galloyl quercetin-3-O-glucoside (5), galloyl quercetin-3-O-rhamnoside (6), quercetin-3-O-rhamnoside (7), kaempferol-3-O-glucoside (13), galloyl kaempferol-3-O-glucoside (14),hydropiperoside (31), vanicoside A (34), vanicoside B (35), vanicoside D (38), rhamnetin (87), apigenin-3-O-glucoside (89) and kaempferol rutinoside (90). From the ethyl acetate fraction, six compounds; 1, 3, 5, 7, 87 and 3,5-dihydroxy-4-methoxybenzoic acid (88) have been isolated and identified using NMR spectroscopy. Phytochemical investigation of the bioactive butanol fraction of P. hydropiper using LC-DAD-ESIMS/MS led to the identification of nine compounds including rhamnazin-3-sulphate (91), quercetin-3-O-glucuronide (8), luteolin-3-O-glucoside (92), kaempferol-3-O-sulphate (93), quercetin-3-O-rhamnoside (7), apigenin-3-O-glucoside (89), quercitrin 7-sulphate (94), luteolin-7-sulphate (95) and isorhamnetin-3-sulphate (persicarin) (96). All compounds were relatively identified based on the MS/MS and UV data in comparison with those of the standard compounds.